Reduced thrombin binding and aggregation in Bernard-Soulier platelets. - Jamieson, G A (1978)
Platelets from two patients with Bernard-Soulier disease showed a reduction in their ability to bind human thrombin. Thrombin binding studies in the high affinity range showed 1,500 sites for the Bernard-Soulier platelets as against 4,000 for normal controls. However, the dissociation constant was the same for both normals and patients (4.4 nM) indicating identical affinity for thrombin at the available sites. In the low affinity range, the Bernard-Soulier platelets showed 8,800 thrombin binding sites as against 24,000 for the controls, but again with identical values of Kd (37 nM). In addition, platelets from these Bernard-Soulier patients showed a decreased rate of aggregation with thrombin at both optimal (300 mU/ml) and suboptimal (60 and 120 mU/ml) thrombin concentrations. The decreased amount of thrombin which can bind to Bernard-Soulier platelets and the decrease in thrombin-induced aggregation may partly explain the hemostatic defect in these patients. In addition, the identical ratios of high affinity and low affinity binding sites in normals and in patients (0.37 and 0.36, and 0.36, respectively) supports the idea of a single class of binding sites for thrombin on the platelet surface.